Enteromorpha prolifera soluble dietary fiber alleviates ulcerative colitis through restoration of mucosal barrier and gut microbiota homeostasis - Ding, Yuan-Yuan; Tang, Xin-Yi; Tian, Yu; Zhang, Feng-Long; Ding, Xiang; Qi, Meng-Chun; Dong, Wei; Liu, Chen-Guang (Frontiers in Nutrition, 2025)
BackgroundUlcerative colitis (UC), a recurrent chronic colon inflammation, presents substantial therapeutic challenges due to the frequent adverse effects associated with conventional pharmacological treatments. These limitations underscore the critical need for developing alternative dietary interventions with improved safety profiles. The present study investigated the therapeutic potential of Enteromorpha prolifera soluble dietary fiber microparticles (EDFM) in UC management, focusing on restoring mucosal barrier integrity and modulating gut microbiota homeostasis.MethodsEDFM was fabricated through aqueous extraction of E. prolifera soluble dietary fiber via boiling followed by spray-drying. A mouse UC model was induced by dextran sulfate sodium (DSS). The severity of UC was evaluated through daily disease activity index (DAI) scoring; quantification of pro-inflammatory cytokines (TNF-α, IL-1β) via ELISA; histopathological analysis of colon sections with H&E staining; immunofluorescence detection of tight junction proteins (ZO-1, occludin); and 16S rRNA sequencing for gut microbiota.ResultsEDFM treatment significantly reduced the expression of pro-inflammatory cytokines (TNF-α and IL-1β), enhanced the expression of tight junction proteins (ZO-1 and occludin), and stimulated mucin (MUC2) production. Additionally, EDFM promoted the proliferation of beneficial probiotics (Alloprevotella, Lachnospiraceae_NK4A136_group, and Ruminococcaceae_UCG-014), while inhibiting pathogenic bacteria (Escherichia-Shigella, Parabacteroides, Rikenellaceae_RC9_gut_group, Odoribacter, and [Ruminococcus]_torques_group).ConclusionEDFM supplementation significantly ameliorates UC through dual modulation of gut microbiota and intestinal barrier integrity, indicating its potential as a functional food ingredient for UC prevention and treatment.